Establishment of the Investment Account. (Policy Papers; Policy Paper ;, 2006)
This paper summarizes the relevant considerations and presents decisions for the establishment of an Investment Account (IA). Executive Directors considered an analysis of the establishment and operations of an IA in September 2005. During the discussion in March 2006 of the medium-term outlook for the Fund's income, Directors requested staff to return to the Board with a paper proposing decisions on the establishment of an IA.